2019
DOI: 10.1016/j.actamat.2019.07.047
|View full text |Cite
|
Sign up to set email alerts
|

Direct TEM observation of α/γ interface migration during cyclic partial phase transformations at intercritical temperatures in an Fe-0.1C −0.5Mn alloy

Abstract: The kinetic behaviour of austenite/ferrite interfaces in a low carbon e 0.5 mass% Mn containing steel during Cyclic Partial Phase Transformation (CPPT) experiments has been investigated using hot stage Transmission Electron Microscopy (TEM). Individual interfaces were observed to display behaviour typical of CPPT experiments as recorded in macroscopic dilatometry experiments and demonstrated i) the "normal", ii) inverse transformations and iii) a stagnant stage in which the interface migrates at a very low vel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…During the stagnant stage, which has been attributed to a significant interfacial enrichment of Mn, [33,34] the interface was observed to maintain a more consistently straight morphology like that seen in the present experiments. [31] 2D phase field simulations of the d-ferrite-to-austenite transformation by Sato et al [4] provide a useful point of comparison with the present study. While there are some differences, there is qualitative agreement between the observed behavior and the simulated behavior as the pinning effect developed.…”
Section: Discussionsupporting
confidence: 53%
See 4 more Smart Citations
“…During the stagnant stage, which has been attributed to a significant interfacial enrichment of Mn, [33,34] the interface was observed to maintain a more consistently straight morphology like that seen in the present experiments. [31] 2D phase field simulations of the d-ferrite-to-austenite transformation by Sato et al [4] provide a useful point of comparison with the present study. While there are some differences, there is qualitative agreement between the observed behavior and the simulated behavior as the pinning effect developed.…”
Section: Discussionsupporting
confidence: 53%
“…Previous in situ TEM studies of the austenite-to-ferrite transformation [28,31] showed that during the normal transformation, there can be local variations in the morphology of the interface varying between curved and nearly straight. During the stagnant stage, which has been attributed to a significant interfacial enrichment of Mn, [33,34] the interface was observed to maintain a more consistently straight morphology like that seen in the present experiments.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations